Efeito do uso de micronutrientes e bioestimulantes em tratamento de sementes na cultura da soja – Região de Belterra - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Soybean is a crop of great importance worldwide and widely used in agribusiness. The increase in production is caused not only by the increase in cultivated areas, but also by the development of cultural treatments such as seed treatment with nutrients and biostimulant, which contribute to high production. The present study aimed to evaluate the effects of seed treatment with micronutrients and biostimulants in different combinations on soybean in an experimental area, in Belterra - PA, in the 2020/21 harvest. The design used was randomized blocks with six treatments: Control, CMZ®, Supa Moly CoMo®, CMZ®+Booster®, CMZ®+ Broadacre Mn® and CMZ®+Booster®+Broadacre Mn® and four replicates, each replicate consisting of 14 lines spaced at 0.5 m. The variables analyzed were Total Grain Mass (MGT), Thousand Grain Mass (MMG) and Productivity, normal data were analyzed by Tukey's Test at 5% probability, with comparison of means. CMZ®+ Broadacre Mn® obtained the highest result for MGT with 1567.50 g, Control and CMZ® obtained the highest MMG with 189.50g and CMZ®+Booster®+Broadacre Mn® reached the highest productivity with 5,167 kg ha-1.
Keywords: Soja; Tratamento de sementes; Micronutrientes; CNPQ:: CIÊNCIAS AGRÁRIAS